Experimental study on flow past two inclined flat plates in tandem arrangement - Teimourian, Amir; Hacisevki, Hasan; Bahrami, Arian (Elsevier Science Bv, 2017)
In this study vortex shedding phenomenon behind two inclined flat plates in tandem arrangement have been studied experimentally. Velocity field components were acquired by employing of Hot-wire Anemometer (HWA) for successive phases in a vortex shedding cycle at Reynolds number Re = 21,000, at three angles of attack 45 degrees, 60 degrees and 75 degrees. The effects of gap ratio between the plates (g/D) together with angle of attack (alpha) on the asymmetric flow structure, time averaged wake flow properties and coherent structures have been investigated. Strouhal number s(t) decreases monotonically with increasing angle of attack, whereas, Modified Strouhal number s'(t) (based on the projected plate width as the characteristic length) is independent of angle of attack. Phase averaged contour shows significant lateral momentum transfer to a growing vortex 1/4 period after a vortex was shed. The result of coherent structure shows a train of opposite vortices, with unequal coherent strength, are being shed alternating from leading edge and trailing edge of the plates.
Keywords: Vortex shedding; Inclined flat plate; Interacting wake; Tandem arrangement